Perspektif Hukum Positif Terhadap Manajemen Dana Wakaf oleh Yayasan - Agung Taufik Wahyuda; Fauhan Thirafi; Muhammad Rizki Firmansyah; Faiz Nayla Chasnun; Rindur Rodiah (Lembaga Pengembangan Kinerja Dosen, 2024)
To manage waqf goods, foundations which are social legal entities can act as nazhir. Waqf assets can be managed effectively by foundations, but distribution must still take into account the interests of waqf recipients in accordance with the waqf pledge agreement. Examining the extent to which foundations effectively supervise waqf in relation to the Foundation Law and the Waqf Law is interesting. This paper uses normative legal techniques to investigate this problem. According to Article 26 Paragraph (3) of the Foundation Law, foundations have the task of managing waqf assets; Thus, waqf legal regulations can be applied. The Waqf Law allows foundations to function as nazhir. Waqf assets must be developed and managed by the foundation that organizes the waqf by carrying out profitable commercial operations in accordance with Waqf Law.